Maturação e germinação de embriões somáticos do mamoeiro 'Golden THB' - Chagas, Kristhiano (2014)
This work aimed to evaluate the maturation and germination of somatic embryos of papaya 'Golden THB'. To obtain the somatic embryos, cotyledons of seedlings of papaya obtained from in vitro germination in MS basal medium, were inoculated into induction medium containing MS salts; myo-inositol (0.55 mM), sucrose (87.5 mM), agar Vetec ® (8 g L-1) supplemented with 4 -CPA (p-chlorophenoxyacetic acid) (25 mM). After 50 days, the calli were transferred to maturation medium: Experiment 1 (MM1) consisting of MS medium, ABA (0.5 mM, CA (15 g L-1) and the treatments supplemented with different concentrations of PEG 6000 (0, 40, 50, 60 and 70 g L-1) for 45 days; Experiment 2 (MM2), consisting of MS medium, ABA (0.5 mM), CA (15 g L -1) and the supplemented treatments different concentrations of malt extract (0.0, 0.1, 0.2, 0.3 and 0.4 g L-1). During 45 days the treatments consisted of four replicates of three Petri dishes of 100 mm × 20 mm, containing four calli. The normal cotyledonary embryos generated in MM2 supplemented with ABA (0.5 mM), CA (15 g -1) and malt extract (0.2 g L-1) were transferred to the germination medium (GM) L formed by the total concentration of medium MS salts, sucrose (87.5 mM), myo- inositol (0.0, 0.275, 0.550 and 0.825 mM) and agar Vetec ® (8 g L-1). The data were subjected to analysis of variance and means studied by regression analysis. Treatment with PEG were lower and harmed the process of formation of embryos and their use at a concentration of 70 g L-1 reduces by 31.85% of the total production and normal somatic embryos of papaya 'Golden THB'. So for somatic embryogenesis of papaya 'Goden THB' not recommended in the maturation medium containing PEG 6000. Adding malt extract (0.17 g L-1) in the maturation medium potentiated the embryonic development of papaya 'Golden THB', 45.40 ES callus-1. Identify the occurrence of secondary somatic embryogenesis and the formation of abnormal somatic embryos. The supplementation of myo-inositol (0.45 mM) in MS medium yielded significant gains in the percentage of germination of somatic embryos and conversion into plantlets papaya 'Golden THB'.